An Improved Micromechanical Framework for Saturated Concrete Repaired by the Electrochemical Deposition Method considering the Imperfect Bonding - Qing Chen; Zhengwu Jiang; Hehua Zhu; J. Woody Ju; Zhiguo Yan; Yaqiong Wang (Journal of Engineering)
The interfaces between the deposition products and concrete are not always well bonded when the electrochemical deposition method (EDM) is adopted to repair the deteriorated concrete. To theoretically illustrate the deposition healing process by micromechanics for saturated concrete considering the imperfect interfaces, an improved micromechanical framework with interfacial transition zone (ITZ) is proposed based on our recent studies. In this extension, the imperfect bonding is characterized by the ITZ, whose effects are calculated by modifying the generalized self-consistent model. Meanwhile, new multilevel homogenization schemes are employed to predict the effective properties of repaired concrete considering the ITZ effects. Moreover, modification procedures are presented to reach the properties of repaired concrete with ITZs in the dry state. To demonstrate the feasibility of the proposed micromechanical model, predictions obtained via the proposed micromechanical model are compared with those of the existing models and the experimental data, including results from extreme states during the EDM healing process. Finally, the influences of ITZ and deposition product on the healing effectiveness of EDM are discussed based on the proposed micromechanical model.